Assessing Students’ Entrepreneurial Interest Post Covid -19 Pandemic - Chrisna Riane Opod; Nikolas F. Wuryaningrat (AIBPM Publisher, 2022)
This study analyses the influence of entrepreneurship education and family background on entrepreneurial interests. The sample of this study is 6th-semester students, Faculty of Economics and Business, Manado State University, who have received entrepreneurship classes. A total of fifty respondents answered the questionnaire thoroughly. Multiple linear regression tests were carried out to prove the hypothesis obtained from the review literature. Based on the research and discussion results, it can be concluded that the factor of entrepreneurship education influences interest in entrepreneurship. In contrast, the family background factor does not influence the Interest in entrepreneurship. Meanwhile, simultaneously entrepreneurial education and family background affect entrepreneurial Interest. It is undeniable that the COVID-19 pandemic had weakened the Indonesian economy, but not with Interest in entrepreneurship. Looking at the result of research that found that entrepreneurship education influences the Interest in entrepreneurship for students, it is necessary to pay more attention to lectures on entrepreneurship, and a better program can be developed. Keywords: Entrepreneurial Education, Entrepreneurial Interest, Family Background, Manado State University, Multiple Linear Regression.